THE POSSIBLE BENEFICAL EFFECT OF AMPELOPSIN ON INJURIES OF OVARIAN AND LUNG TISSUES GENERATEDBY OVARIAN TORSION/DETORSION - E. P. Topdağı Yılmaz; A. Tanyeli; F. N. Ekinci Akdemir3; M. C. Güler; E. Eraslan (Journal of Animal and Plant Sciences, 2020)
Purpose: The aim of this study is to investigate the effects of ampelopsin (AMP) on injuries of ovarian and lung tissues generated by bilateral ovarian torsion/detorsion (TD) model in rats. Material and Methods:In the present study, 32 Sprague Dawley female rats were randomly divided into four groups. Groups planned as sham, TD, 80 mg/kg dose of AMP+TD, and 160 mg/kg dose of AMP+TD. In the sham group, the abdomen was opened applying an incision and closed again without TD model. In TD group, 3 hours of torsion followed 3 hours of detorsion were made. In the 80 and 160 mg/kg dose groups, respectively, AMP was given orally 80 and 160 mg/kg doses before detorsion and TD was performed as defined in TD group. At the end of detorsion period, rats were sacrificed and the ovarian and lung tissues were quickly removed. All results were analyzed using statistically appropriate tests. Results and Conclusion: Malondialdehyde (MDA) level, myeloperoxidase (MPO) activity, tumor necrosis faktor-α (TNF-α), interleukin-1beta (IL-1β), total oxidant status (TOS) and oxidative stress index (OSI) values increased significantly in TD group when compared to sham group (p<0.05). However, superoxide dismutase (SOD) enzyme activity and total antioxidant status (TAS) values decreased in ovarian and lung tissues of TD group. Conversely, SOD enzyme activity increased, while TOS and OSI values, MPO activity and TNF-α, IL-1β, MDA levels decreased significantly due to administration of AMP in 80 and 160 mg/kg dose groups (p<0.05). As a conclusion, in this study, it was demonstrated that 80 and 160 mg/kg doses of AMP administrations protected against oxidative damage of the ovarian and lung tissues that generated by experimental TD in rats.
Keywords: Ampelopsin; Torsion/Detorsion; Ovary; Lung; Rat